# Algebra II

posted by .

Factor out:
64x^3 + 1

It is a binomial times a trinomial
(4x+1)(16x^2-4x+1) should work. Check my math again!

[8x^(3/2) - i][8x^(3/2) + i]

Although my previous answer works (if i = sqrt-1), Taasha's is what you are looking for.

## Respond to this Question

 First Name School Subject Your Answer

## Similar Questions

1. ### algebra

Can someone please help me with this one?
2. ### math

Consider the following binomials. A=(x^2+5x) B=(6x+30) Part 1: Factor each binomial by finding the GCF. Then, add the two factored binomials to make a single expression. Part 2: Now add the original forms of binomial A and B together …
3. ### math

Consider the following binomials. A=(x^2+5x) B=(6x+30) Part 1: Factor each binomial by finding the GCF. Then, add the two factored binomials to make a single expression. Part 2: Now add the original forms of binomial A and B together …
4. ### Algebra Please Check answers

Directions: Determine whether each trinomial is a perfect square. If so, factor it. 2. 4a^2+4a+1 Answer: 2(a+1)^2 3. 9m^2+15m+25 Answer: no 4. d^2-22d+121 Answer: (d-11)^2 Directions: Determine whether each binomial is the difference …
5. ### math 118

x^2+10x Add the proper constant to the binomial so tha tthe resulting trinomial is a perfect square trinomial. Then factor the trinomial
6. ### Math

find any stationary points of the function g(x) = (2x-3)square root of 5+16x-4x^2 (0 less than or equal to x less than or equal to 4) and use the first derivative test to classify each stationary point as a local maximum or local minimum …
7. ### algebra 2

this binomial can be factored as the product of a binomial and trinomial. Enter the binomial factor. 64y^15 + 125
8. ### algebra

the binomial 8y^12+z^6 can be factored into a binomial and a trinomial. the binomial factor is (2y^4+z^2). whats the trinomial?
9. ### Algebra 1 Answer Check

Factor this trinomial. -16x + 20x + 6 A: -2(4x + 1)(2x - 3)
10. ### 9th grade algebra (completing square)

Can you check the following? A1. (2x + 3)^2 = 25 sqrt(2x + 3)^2 = +-sqrt(25) 2x + 3 = +- 5 2x + 3 = 5, 2x + 3 = -5 2x = 2, 2x = -8 x = 1, x = -4 {-4, 1} A2. x^2 + 14x + 45 = 0 x^2 + 14x + __ = -45 + __ x^2 + 14x + 49 = -45 + 49 (x

More Similar Questions